Primary Healthcare Renewal in Canada: Not There Yet - Alan Katz (Law & Governance, 2008)
[This article was originally published in HealthcarePapers, Volume 8, Number 2.] The organization of primary care service delivery in Canada has changed dramatically since the turn of century, spurred on by significant investment from both provincial and federal governments. The sustainability of this change is not yet guaranteed, and further investment in information technology and change management is required to create an integrated primary healthcare system.